Implementasi Model Pembelajaran Cooperative Learning Dalam Mewujudkan Pembelajaran Humanistik Pada Pelajaran Aqidah Akhlak Kelas IX Di Madrsah Tsanawiyah Hidayatul Mubtadiin - Ass Miana Solehah; Dewi Yanti; Mustaqim Hasan (Journal on Education, 2023)
The Implementation of Cooperative Learning Model in Realizing Humanistic Learning on Aqidah Akhlak Lesson in Hidayatul Mubtadiin Islamic Junior High School Jati Agung, South Lampung Academic Year 2022/2023 is a study aimed to apply the Cooperative Learning model in Aqidah Akhlak learning and realize humanistic learning. Cooperative Learning is a cooperative learning model that prioritizes the activity and cooperation among students in achieving common goals. In this learning model, students are given the opportunity to discuss and exchange information with their peers, resulting in an interactive learning process. The results of this study show that the implementation of Cooperative Learning model can increase the engagement and participation of students in learning, as well as realize humanistic learning that can shape the character and morals of students.